2010
DOI: 10.1002/adfm.200901971
|View full text |Cite
|
Sign up to set email alerts
|

Vertical (La,Sr)MnO3 Nanorods from Track‐Etched Polymers Directly Buffering Substrates

Abstract: A novel and general methodology for preparing vertical, complex‐oxide nanostructures from a sol–gel‐based polymer‐precursor solutions is developed using track‐etched polymers directly buffering substrates. This method is able to develop a nanostructure over the entire substrate, the dimensions and localization of the vertical nanostructures being preset by the polymeric nanotemplate. Thereby, nanostructures with lateral sizes in the range of 100 to 300 nm and up to 500 nm in height have been grown. Two example… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…The absence of manganese in the nanodots indicates that the generated nanostructures were actually not LSMO, rather a lanthanum strontium oxide. This was not a wholly unexpected result due to other reported work showing the migration of manganese out of LSMO nanostructures [3]. The possibility that manganese is lost during the electron beam writing process, or the developing step should also be considered, and is under study.…”
Section: Nanodots Growthmentioning
confidence: 73%
See 1 more Smart Citation
“…The absence of manganese in the nanodots indicates that the generated nanostructures were actually not LSMO, rather a lanthanum strontium oxide. This was not a wholly unexpected result due to other reported work showing the migration of manganese out of LSMO nanostructures [3]. The possibility that manganese is lost during the electron beam writing process, or the developing step should also be considered, and is under study.…”
Section: Nanodots Growthmentioning
confidence: 73%
“…Since many functional properties rely on epitaxial order and crystal orientation (e.g., piezoelectric and high-T C superconducting properties), growth methods that are able to provide ordered arrays of epitaxial nanostructures are highly interesting. Several recent studies in our group have grown epitaxial single crystalline functional oxide nanostructures on single crystal substrates [3][4][5]. However, these nanostructures were generated with no precise position control.…”
Section: Introductionmentioning
confidence: 98%
“…Otherwise, when the fluid is a polymer solution of high viscosity, a wall wetting process occurs, giving rise to nanotubes formation upon solvent evaporation and crystallization at high temperatures, as in the present system. However, we recently showed that the same precursor solution may have a very different wetting behaviour when filling track etched porous polymer templates with low surface tension, there giving rise to the formation of nanorods [11][12][13].…”
Section: Resultsmentioning
confidence: 98%
“…[1][2][3][4]. Recently, increasing efforts have been made to synthesize and understand the growth of one-dimensional nanostructures, such as nanotubes and nanowires of these materials due to their promising potential applications in spintronics, transducers or sensors in future nanoscale devices while retaining unique properties due to size confinement in the radial direction [5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…For correlated pinning, extended defects of controlled orientation are preferred, and in particular for YBCO, c-axis pinning is of particular interest as this field orientation typically determines the minimum in-field , which is a limiting factor for many applications. Several approaches to introduce pinning sites ex-situ have been investigated, such as heavy ion irradiation [5] and nanorod deposition on substrates prior to YBCO deposition [6]. On the other hand, in-situ techniques most frequently involve precipitation of second phase particles, by varying the YBCO stoichiometry or introducing other rare-earth elements [7], formation of self-assembling precipitates [8], addition of nano-sized secondary particles [9]- [11] or interlayer formation [12].…”
Section: Introductionmentioning
confidence: 99%